(untitled) (Biological Sciences - PJSIR, 1999)
The essential oil obtained by hydrodistillation of the fruits from Thuja orientalis at two stages was analysed by GC and GC/MS. Among the compounds indentified, a-pinene (41.48-45.61 %), N-carene (32.69-34.55) -terpinene (2.28-2.51 %), p-eymene (1.29-2.23%), cedrol (1.82-4.50%), camphene (1.78-1.96%), D-Iimonene (1.47.2.40%) and myrtenol 0.27-4.40%) were found to predominate, while other compounds were either in small quantities (i.e. less than 1%) or in traces.